PEMAHAMAN GOOGLE CLASSROOM PESERTA DIKLAT SUBTANTIF PENINGKATAN KOMPETENSI MULTIMEDIA DI KEMENTERIAN AGAMA KABUPATEN TASIKMALAYA - Saeful Nurdin (Tatar Pasundan : Jurnal Diklat Keagamaan, 2019)
The purpose of this study was to determine the increase in understanding of google classroom as multimedia learning with the blended learning method. Utilizing google classroom can help with the collection of tasks, very efficient in terms of costs and users. The design used was a one-group pretest-posttest design, the sample was 30 subject mater teachers assigned to Madrasah Tsanawiyah at the Ministry of Religion in Tasikmalaya regency. The results of the pretest with an average value of 47 and posttest 76 on a scale of 100, while the normalized gain value is at the value of 0.53 with the medium category, it can be said there is an increase in understanding of google classroom in the substantive training of increasing multimedia competency. Keywords: google classroom, understanding, blended learning